Proposal to amalgamate the national and university libraries in Reykjavik and to build a new national and university library: Iceland - (mission) November 1970 - Carter, Edward J.; Tveterås, Harald L. (1971)
Mission report concerning amalgamation of two libraries: the national library and the university library of Reykjavik, Iceland